Budaya Politik Emha Ainun Nadjib dalam Meretas Problematika Pluralitas Agama di Indonesia - Ismail Angkat (Sekolah Tinggi Agama Islam Sumatera Medan, 2021)
Indonesia is a plural country of religion, race, ethnicity and culture. Apart from being a wealth of plurality, it is also a challenge, because plurality is prone to causing conflict. Religious diversity (including local religion) also makes Indonesia has the same vulnerability. For this reason, Emha Ainun Nadjib has a holistic view of how this diversity is realized and managed. This study aims to analyze Emha Ainun Nadjib's culture in hacking religious life in Indonesia. By using a qualitative approach and the theory of plurality and politics, the author maps the thoughts of Emha Ainun Nadjib in addressing these issues. The results showed that Emha Ainun Nadjib viewed plurality as an invaluable gift from God. Based on this phenomenon, Emha Ainun Nadjib provides understanding and builds awareness of the Indonesian people in processing diversity into a strength. Emha uses a political culture approach to break the chain of conflict generated by diversity into harmony.